THEORY, HISTORY, AND PRACTICE OF EDUCATION: FIN DE SIÈCLE AND A NEW BEGINNING - Edwards, Reginald (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1991)
The history and development of normal schools is traced through a summary of events that transpired in France, the United States, Britain, and Canada. The author examines the roots of several systems of teacher training and identifies specific institutions (normal schools) that played an important role in bringing to McGill University key persons interested in the training of teachers. Much of the article is devoted to linking the diverse influences that culminated in the establishment of the McGill Normal School, the Macdonald College for Teachers, and the Macdonald Chair of Education. While the article outlines the history of McGill's role in teacher education in Quebec and Canada, it also gives a broad perspective on the history of normal schools in Europe and North America, and their influences on teacher education today. RÉSUMÉ L'histoire et le développement des écoles normales est retracée par un résumé des événements qui se sont produits en France, aux États-Unis, en Grande-Bretagne et au Canada. L'auteur analyse les racines de plusieurs systèmes de formation des maîtres et se penche sur certains établissements (écoles normales) qui ont contribué àfaire venir à l'Université McGill des personnes clés s'intéressant à la formation des maîtres. Une bonne part de l'article est consacré aux diverses influences qui ont abouti à la création de la McGill Normal School, du Macdonald College for Teachers et de la Chaire Macdonald des sciences de l'éducation. Si l'auteur dresse l'historique du rôle joué par McGill dans laformation des maîtres au Québec et au Canada, il propose une vue d'ensemble plus étendue de l'historique des écoles normales en Europe et en Amérique du Nord et de leurs incidences sur la formation des maîtres telle qu'elle est dispensée aujourd'hui.